In vitro standardization of two different removal devices in cemented implant prosthesis. Issue 8 (27th July 2015) - Schierano, Gianmario; Manzella, Carlo; Menicucci, Giulio; Parrotta, Alessio; Zanetti, Elisabetta M.; Audenino, Alberto L.
Abstract: Objectives: The purpose of this study was to describe the force generated by two different removal devices used to retrieve cemented crowns on implant abutments. The influence of six different operators was evaluated. Material and methods: Three replicated Coronaflex ® (Kaltenbach & Voigt GmbH, KaVo Dental GmbH) and reverse hammer setups were tested. The experimental setup has employed a screw bearing a diametral hole through which a loop holder passed. The screw was attached to a force transducer (Brüel & Kjær, type 8201), and the loop holder arm was kept perpendicular to the transducer axis. The results were statistically evaluated with ANOVA. Results: The operator has resulted to play significant influence with reference to reverse hammer (coefficient of variation 43.3%) rather than with Coronaflex ® (9.8%). Evaluating every single operator, more variation can still be found by considering each reverse hammer (37.5%) rather than each Coronaflex ® (8.8%). Conclusion: Coronaflex ® device was found to systematically reach a more repeatable and higher peak amplitude of forces compared with reverse hammer, both by experienced and inexperienced operators.